EP818 Primary debulking surgery versus primary neoadjuvant chemotherapy with or without interval debulking surgery for advanced stage ovarian cancer: a single institute study. (1st November 2019) - Chen, YY; Ou, YC; Lin, H
Abstract : Introduction/Background: Neoadjuvant chemotherapy followed by interval debulking surgery (NACT-IDS) has been recommended as an alternative treatment for selected patients with advanced-stage epithelial ovarian cancer (EOC). The aim of present study was to compare clinical outcomes of primary debulking surgery (PDS) versus NACT with or without IDS in a single institute of women with advanced-stage EOC. Methodology: Retrospective cohort study of women with stage IIIC(T3cN0-1) and IV EOC diagnosed between 2008 and 2016 treated at Kaohsiung Chang Gung Memorial Hospital. Patients who underwent PDS and NACT were identified. The Kaplan-Meier method was used to compare progression-free (PFS) and overall survival (OS) data. Results: A total of 143 newly diagnosed stage IIIC (T3cN0-1)and IV EOC patients were included in the final analysis. 92 women (64.3%) underwent PDS, 33 (23.1%) underwent NACT-IDS, and 18 (12.6%) received chemotherapy alone. The patients who received chemotherapy alone had significantly lower PFS of 4 months and OS of 28 months compared to PDS (PFS:13 months; OS:46 months) and NACT-IDS (PFS: 14 months; OS:28 months) groups, respectively. Conclusion: NACT-IDS did not improve PFS and OS compared to PDS in advanced-stage EOC. Patients received chemotherapy alone had the lowest PFS and OS compared to PDS and NACT-IDS groups. Disclosure: Nothing to disclose.